EPIDEMIOLOGICAL PROFILE OF ACCIDENTS CAUSED BY VENOMOUS ANIMALS IN THE SÃO PATRÍCIO VALLEY (CIPEEX, 2025)
Accidents involving venomous animals are, to a large extent, a significant public health problem, especially in tropical and developing countries. They are one of the main contributors to morbidity and mortality in Brazil and worldwide. Goiás faces significant challenges with venomous animal accidents, recording about 1,200 cases annually, with a fatality rate of approximately 0.7%. Snakes, particularly jararacas and rattlesnakes, are the most frequent, followed by scorpions and spiders. In this context, the São Patrício Valley region, in particular, shows a significant incidence of venomous animal accidents. With its typical cerrado vegetation and hot climate, it is a suitable habitat for venomous snakes such as rattlesnakes; scorpions and spiders are also common in the region, posing risks to the local population.The present study aims to identify the highest incidences of venomous animal accidents in the São Patrício Valley. To explore these issues in more detail, a cross-sectional, quantitative, and descriptive study will be conducted based on secondary data from the São Patrício Valley region. The methodology will be based on using data from the study of the spread of diseases, with an analysis of venomous animal accidents provided through the Information System for Notifiable Diseases (SINAN). All records are entered by the municipalities with the aim of frequently transmitting the information collected by the Epidemiological Surveillance System. The main focus of this study is to analyze the highest occurrences of venomous animal accidents in the São Patrício Valley and the effectiveness of nursing care for patients affected by these incidents.The study will observe the three highest epidemiological incidences during the period from 2019 to 2023 in the São Patrício Valley - GO, consisting of twenty-three municipalities, identifying areas with the highest occurrence. This analysis is important to assess the health resources being utilized, with a focus on preventive measures and specific control programs in the most affected regions (SINAN, 2024). The objective is to create a bibliographic material that highlights the epidemiological aspects related to venomous animal accidents, with an emphasis on the São Patrício Valley region in the state of Goiás. This material will be useful for study and analysis by professionals and students in environmental and health fields, as well as providing an educational contribution to the general public. Additionally, the project aims to describe the history of epidemiology and highlight its importance in the effectiveness of nursing care for patients affected by these incidents. The project seeks to clarify myths about venomous animal accidents, increase awareness, and promote prophylactic actions to reduce the incidence of accidents and prevent serious complications and deaths.
Keywords: accidentes; epidemiology; venomous animals